Pien-Tze-Huang alleviates CCl4-induced liver fibrosis through the inhibition of HSC autophagy and the TGF-β1/Smad2 pathway - Zhang, Yuqin; Hua, Liping; Lin, Chunfeng; Yuan, Mingzhou; Xu, Wei; Raj D., Anand; Venkidasamy, Baskar; Cespedes-Acuna, Carlos L.; Nile, Shivraj Hariram; Yan, Guohong; Zheng, Haiyin (Frontiers in Pharmacology, 2022)
Ethnopharmacological relevance: Pien-Tze-Huang (PZH) - Traditional Chinese Medicine (TCM) compound has been employed to treat various liver inflammation and tumors for over ten decades. Interestingly, most of the pharmacological effects had been validated and explored towards liver ailment along with pro-inflammatory conditions and cancer at the cellular and molecular level till date. Aim of the study: The present study was aimed to investigate the therapeutic effect on PZH autophagy and TGF-β1 signaling pathways in rats with liver fibrosis and hepatic stellate cell line (HSC). Materials and Methods: Male SD rat with carbon tetrachloride (CCl4) induced liver fibrosis was used as the animal model. Next, PZH treatment was given for 8 weeks. Following, the therapeutic effects of CCl4 and PZH were analyzed through hepatic tissue structure and function. Subsequently, mRNA and protein expression were examined by quantitative polymerase chain reaction (qPCR), western blotting and immunohistochemistry (IHC). Then, the cell vitality of PZH treated HSC and the expression of key molecules prevailing to autophagy was studied in vitro. Results: The results revealed the reduced production of extracellular collagen through adjusting the balance of matrix metalloproteinase (MMP) 2, MMP9 and tissue inhibitor of matrix metalloproteinase 1 (TIMP1) in PZH treated CCl4-induced liver fibrosis. Interestingly, PZH inhibited the activation of HSC by down regulating TGF-β1 and phosphorylating Smad2. Furthermore, PZH down-regulated the yeast Atg6 (Beclin-1) and microtubule-associated protein light chain 3 (LC3) toward suppress the HSC autophagy. Conclusion: To conclude, PZH alleviated the CCl4-induced liver fibrosis to reduce the production of extracellular collagen and inhibiting the activation of HSC. Besides, their pharmacological mechanisms related to autophagy and TGF-β1/Smad2 signaling pathways were revealed for the first time.